The Impact of Geopolitical Factors on Achieving International Governance Dimensions in Iraq: Evidence from the Repercussions of the Iran–Israel War (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to determine the impact of geopolitical factors on achieving the dimensions of international management in Iraq in light of the repercussions of the Iran-Israel war. To achieve this goal, the researcher relied on presenting theoretical framework for each of: Regional/geopolitical factors -Traditional and critical geopolitical theories -Importance of traditional and critical geopolitical theories in understanding American strategy within the scope of Iran -Israel -Iraq region (Eurasia) -Heartland theory in understanding strategy -Mahan's sea power theory in understanding strategy - Grand chessboard theory -Clash of civilizations theory and the end of history theory -Geopolitical situation in Iran -Geopolitical situation in Israel -Geopolitical situation in Iraq -Impact of geopolitical factors on crisis management and planning - International management -International management theories -Power shift theory -Structural realist theory -Democratic peace theory -International system convergence theory -Trade and conflict theory -Role theory -Arms race theory -Creative chaos theory -Balance of power theory.To determine relationship between geopolitical factors and realization of dimensions of international management in Iraq in light of the repercussions of the war between Iran and Israel. Questionnaire distributed to a sample of 150 faculty members from the Faculties of Management and Faculty of Economics and Political Science in various categories including: Lecturer - Assistant Professor -Professor. The data analyzed statistically.Study concluded that there is a relationship between geopolitical factors and the achievement of international management dimensions in Iraq in light of the repercussions of the war between Iran and Israel.
Keywords: Geopolitical Factors; Geopolitical Theories; International Management Theories; Geopolitical Situation in Iran; Geopolitical Situation in Israel Geopolitical Situation in Iraq; Eurasia